Chemical and microbial quality of whey from cow milk using calf rennet, microbial rennet, lactic acid and papaya latex (Bangladesh Journal of Animal Science, 2022)
The purpose of the study was to determine the quality of whey obtained from cow milk using different types of coagulants (microbial rennet, calf rennet, lactic acid and papaya latex). The quality of whey was evaluated with the help of chemical and microbial tests. Results revealed that maximum whey yield (765 mL/L milk) was obtained from lactic acid coagulation which was 17 mL higher than that of the microbial rennet coagulation (p=0.000). The pH was found significantly (p